The mammoth from the archaeo-paleontological hominin site of Huéscar-1: A tile in the puzzling question of the replacement of Mammuthus meridionalis by Mammuthus trogontherii in the late Early Pleistocene of Europe - Ros-Montoya, Sergio; Palombo, Maria Rita; Espigares-Ortiz, María Patrocinio; Palmqvist-Barrena, Carlos Paul; Martínez-Navarro, Bienvenido (Elservier, 2018)
The site of Huéscar-1 (Baza basin, Granada, Spain) yielded an interesting paleontological record close in age to the Early-Middle Pleistocene boundary. In 2003 two lithic artifacts were found, confirming the human presence at this site. The faunal assemblage preserves few marsh turtle remains, a number of avian species, and small and large mammals, including some elephant remains believed in the past to record the oldest appearance in Europe of Palaeoloxodon antiquus. They actually belong to the genus Mammuthus, although the identification (i.e., Mammuthus meridionalis or Mammuthus trogontherii) has been questioned. The aim of this research is two folded: (1) to provide a new description of Huéscar-1 remains, which can confidently be attributed to the southern mammoth, thus representing one among the last populations of M. meridionalis recorded in Europe; and (2) to briefly discuss open questions about time and mode of the replacement of M. meridionalis by M. trogontherii by the end of the Early Pleistocene.
https://openpolicyfinder.jisc.ac.uk/id/publication/4700
Keywords: Mamuts; Elefantes fósiles; Paleontología - Pleistoceno; Early - Middle Pleistocene transition; Mammuthus meridionalis; Mammuthus trogontherii; Palaeoloxodon antiquus; Southern Europe